Acinetobacter ursingii peritonitis in a patient on peritoneal dialysis (PD): case report and literature review - R. Haridian Sosa Barrios; Reiny S. Verastegui Albites; Mariana López Quiroga; Cristina Campillo Trapero; Milagros Fernández Lucas; Maite E. Rivera Gorrín (BMC Nephrology)
Abstract Background Peritonitis is a frequent complication of PD that can lead to technique discontinuation and increase morbidity and mortality. It is caused mainly by gram-positive bacteria (up to 70%); however, gram-negative organisms usually have relatively poor outcomes. Among gram-negative bacteria, Acinetobacter is rare, especially Acinetobacter ursingii. Case report We report the third case of PD peritonitis caused by Acinetobacter ursingii, treated with directed intraperitoneal antibiotics with good clinical response and favorable outcome. Conclusion Although Acinetobacter ursingii is rare, it is potentially harmful because of its challenging identification and antibiotic resistance with therapeutic consequences, requiring at least two antibiotics and careful follow up. Keeping in mind that it is ubiquitous, careful technique, training/retraining seems highly recommended.